A Biomimetic Approach for Spatially Controlled Cell Membrane Engineering Using Fusogenic Spherical Nucleic Acid. (25th November 2021) - Lin, Minjie; Chen, Yuanyuan; Zhao, Sisi; Tang, Rui; Nie, Zhou; Xing, Hang
Abstract: Engineering of the cell plasma membrane using functional DNA is important for studying and controlling cellular behaviors. However, most efforts to apply artificial DNA interactions on cells are limited to external membrane surface due to the lack of suitable synthetic tools to engineer the intracellular side, which impedes many applications in cell biology. Inspired by the natural extracellular vesicle‐cell fusion process, we have developed a fusogenic spherical nucleic acid construct to realize robust DNA functionalization on both external and internal cell surfaces via liposome fusion‐based transport (LiFT) strategy, which enables applications including the construction of heterotypic cell assembly for programmed signaling pathway and detection of intracellular metabolites. This approach can engineer cell membranes in a highly efficient and spatially controlled manner, allowing one to build anisotropic membrane structures with two orthogonal DNA functionalities. Abstract : Inspired by the natural extracellular vesicle‐cell fusion process, we introduced the fusogenic spherical nucleic acid (fuso‐SNA) to achieve spatially controlled cell membrane engineering with DNA by using a liposome fusion‐based transport (LiFT) approach. We demonstrated asymmetric DNA modifications on the cell membrane with orthogonal functionalities on each side, realizing applications such as heterotypic cell assembly and intracellular metabolites detection.